The trial and error method - Hawley, J. (Sportscience)
Authors profile one of the greatest coaches, they analyze and salute one of them, Arthur Lydiard, and his training philosophy. Summing Up: "Long even-paced running at strong speed increases strength and endurance, even when it is continued close to the point of collapse." "Successful training is intelligent training. Intelligent training is knowing the why of an exercise, as well as the what and how."